2022
DOI: 10.3390/ijms23137251
|View full text |Cite
|
Sign up to set email alerts
|

Dipotassium Glycyrrhizinate on Melanoma Cell Line: Inhibition of Cerebral Metastases Formation by Targeting NF-kB Genes-Mediating MicroRNA-4443 and MicroRNA-3620—Dipotassium Glycyrrhizinate Effect on Melanoma

Abstract: Glycyrrhizic acid (GA), a natural compound isolated from licorice (Glycyrrhiza glabra), has exhibited anti-inflammatory and anti-tumor effects in vitro. Dipotassium glycyrrhizinate (DPG), a dipotassium salt of GA, also has shown an anti-tumor effect on glioblastoma cell lines, U87MG and T98G. The study investigated the DPG effects in the melanoma cell line (SK-MEL-28). MTT assay demonstrated that the viability of the cells was significantly decreased in a time- and dose-dependent manner after DPG (IC50 = 36 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, studies showed that GL inhibited the metastasis of melanoma cells by regulating T helper type 2 (Th2) cell resistance, interfering with further the dissemination of melanoma ( Kobayashi et al, 2002 ; Su et al, 2017 ). Dipotassium of GL inhibited the metastases of melanoma Cells into brain ( Bonafe et al, 2022b ).…”
Section: Roles Of Gl In Cancer Therapymentioning
confidence: 99%
“…Furthermore, studies showed that GL inhibited the metastasis of melanoma cells by regulating T helper type 2 (Th2) cell resistance, interfering with further the dissemination of melanoma ( Kobayashi et al, 2002 ; Su et al, 2017 ). Dipotassium of GL inhibited the metastases of melanoma Cells into brain ( Bonafe et al, 2022b ).…”
Section: Roles Of Gl In Cancer Therapymentioning
confidence: 99%
“…In accordance with the results observed in the present study, another recent study has suggested that DPG has an apoptotic, anti-proliferative, and anti-migratory effect on the melanoma cell line (SK-MEL-28) bearing the BRAF mutation. DPG was also able to inhibit cancer stem-like cells that may cause cerebral tumor formation ( 39 ). In addition, DPG treatment has shown that SK-MEL-28 cells also presented a significantly higher level of miR-4443 and miR-3620 expression than control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the migration of SK-MEL-28 cells stimulated by 12-O-tetradecanoylphorbol-13-acetate (TPA) was attenuated by adding DPG by wound-healing assay. In addition, the MMP-9 expression level was inhibited by DPG in melanoma cells stimulated by TPA and compared to only TPA-treated cells ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, GA can be widely used to treat many diseases, including melanoma (Su et al., 2017). There are some studies that GA can promote apoptosis, inhibit proliferation, and block migration of melanoma SK‐MEL‐28 cells (Bonafe et al., 2022; Song et al., 2013). The anticancer effect of GA is mainly achieved through inhibiting proliferation, migration, metastasis, and angiogenesis as well as inducing autophagy, apoptosis, DNA damage, and cell cycle arrest (Hussain et al., 2018; Shi et al., 2021).…”
Section: Introductionmentioning
confidence: 99%